Fractional-Order Sliding Mode with Active Disturbance Rejection Control for UAVs - Zhikun Zhang; Hui Zhang (Applied Sciences)
This paper investigates the attitude control problem of unmanned aerial vehicles (UAVs), especially in the presence of uncertainties and external disturbances. To address this challenge, a fractional-order reaching law sliding mode with active disturbance rejection controller (FOSM-ADRC) is proposed. The controller combines a fractional-order calculus operator and active disturbance rejection controller (ADRC) techniques to enhance the dynamic performance and robustness of the system. Through the inner and outer loop design, the jitter of the sliding mode controller (SMC) is effectively suppressed, and fast response and strong anti-jamming ability are achieved, which, in turn, improves the control accuracy. Firstly, the dynamic model of the UAV is established, and its nonlinear dynamic characteristics are analyzed in detail. On this basis, a fractional-order reaching law sliding mode controller (FO-SMC) is designed as the outer loop to achieve fast response. ADRC is employed in the inner loop to compensate for the internal and external disturbances of the system. The results show that the FOSM-ADRC can effectively suppress the jitter phenomenon and maintain good control performance.